Transport Safety Agency's Success Indicators: How Well Does a Performance Management System Perform? - Leviakangas, Pekka (Elsevier, 2015)
Whereas transport safety research has long and established traditions, the pivotal public task of integrally governing, managing and overseeing transport safety in an effective and socio-economically cost efficient manner is yet a largely uncharted area within science. Therefore, it should not be taken for granted that all public resources are allocated where they add value the most. This is due in part to historical reasons and the inertia within how governments respond to changes around them. This article investigates the performance management system of a national transportation safety agency with qualitative methods. First, it introduces the evolution history and the surrounding institutional architecture of the agency. Next, the goal-setting, steering and management control mechanisms are described, followed by a cross-check of mandated tasks and objectives and the associated performance indicators. The main finding is that significant gaps between stated policy objectives, operational annual performance targets and available indicators can be identified. Especially with regard to societal objectives, the steering framework turns out to provide less than comprehensive coverage. Performance indicators for some major objectives are missing and vice versa, some measurement metrics do not seem to link clearly to set objectives. Not all the set objectives need (or even could) necessarily be measured, but certain shortcomings in the performance control system may prove critical. The findings imply that there is a risk of sub-optimal use of public resources if the targets and indicators of agencies are not thoroughly considered so that they logically cover agencies' mandates. The implications of the discovered gaps are outlined, together with recommendations for a more balanced approach. The analysis concludes with some recommended steps in order to cover the blind spots. With the aid of these steps, performance management systems can be improved to better meet policy and societal objectives.